2013
DOI: 10.1539/joh.13-0074-oa
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime and Sleep Duration in Relation to Depressive Symptoms among Japanese Workers

Abstract: Bedtime and Sleep Duration in Relation to Depressive Symptoms among Japanese Workers: Nobuaki SAKAMOTO, et al. Department of Epidemiology and Prevention, Center for Clinical Sciences, National Center for Global Health and Medicine— Objectives While bedtime may influence circadian rhythms, potentially leading to depression, epidemiological data on this issue are limited. We cross‐sectionally investigated the association between bedtime and depressive symptoms in Japanese workers, taking sleep duration into cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…For example, the Netherlands Study of Depression and Anxiety revealed that late chronotype (evening-type of sleep) was associated with depressive disorder [ 15 ]. Studies conducted among workers [ 16 ] and freshmen [ 17 ] in Japan showed similar associations between late bedtime and depressive symptoms. Third, sex differences exist in sleep quality, duration, latency, and architecture in the general population [ 18 ]; however, the impact of sex differences in relation to sleep, fish consumption, and depression in the Korean population is not well-understood.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, the Netherlands Study of Depression and Anxiety revealed that late chronotype (evening-type of sleep) was associated with depressive disorder [ 15 ]. Studies conducted among workers [ 16 ] and freshmen [ 17 ] in Japan showed similar associations between late bedtime and depressive symptoms. Third, sex differences exist in sleep quality, duration, latency, and architecture in the general population [ 18 ]; however, the impact of sex differences in relation to sleep, fish consumption, and depression in the Korean population is not well-understood.…”
Section: Introductionmentioning
confidence: 76%
“…A study of almost 16,000 adolescents found an association between earlier parental set bedtime and depression [ 25 ]. Epidemiological studies conducted in Japan reported that late bedtime predicted depression in workers [ 16 ] and university students [ 17 ]. Consistent with those studies, our study found that those who had late bedtime habits were also at a higher risk of having depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent shifts in sleep timing were associated with metabolic problems and increased prevalence of depressive symptoms [18,19]. However, the literature on effects of bedtime on sperm health is scant.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with depression might not think that they have had adequate sleep, so the association between the two is not completely clear. 10 In summation, some lifestyle habits seem to be associated with RAS or RAS-type ulceration as well as mental health. Although it is the commonest oral mucosal disease, the aetiology of RAS remains undefined.…”
Section: Gementioning
confidence: 99%